Safety behavior at work: The role of safety climate and fear of negative evaluation - Mohd Shamsudin, Faridahwati; Subramaniam, Chandrakantan; Alshuaibi, Ahmad Said; Bachkirov, Alexandre (2015)
Safety performance has been measured using two dimensions: safety compliance and safety participation. Though useful, we propose that these dimensions are insufficient to capture what is expected of employees in demonstrating safety behavior at work. We propose that safety reporting is integrated into the current model. Secondly, we seek to examine the role of safety climate on the three proposed facets of safety performance. Thirdly, we also seek to examine the moderating effect of fear of negative evaluation on safety performance and safety climate relationship. This research contributes to the expanding literature on workplace safety.